Pengembangan dan Validasi Media Pembelajaran Video Visual untuk Meningkatkan Motivasi Belajar IPA pada Sistem Gerak Manusia Kelas V - Ramadan, Luthfi; Saputra, Muhammad Faiz; Kurniawati, Wahyu; Husna, Anisa Al (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to develop and validate visual video learning media that can encourage students to learn science, especially the human movement system, in grade V elementary school. To help students understand the subject matter, visual videos that combine audio and visual elements are used. This research uses the Research and Development (R&D) method with a systematic and structured ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The quality of the video, cover design, and materials presented were evaluated by professionals to test the validity of the learning media. The validation results show that the visual video media increases students' understanding and desire to learn. It is expected that the use of this media will help teachers deliver lessons more interestingly and effectively. Research that confirms the importance of innovation in learning media development through evolving technology and interactive effectiveness